BAGAIMANA DRAMA SERI KOREA MEMPENGARUHI PERILAKU PACARAN REMAJA? - KENCANAWATI, DEWA AYU PUTU MARIANA (MIDWIFERY MEDICAL JOURNAL, 2014)
Background: Adolescence is a period in the development of human life. At this time there is so many change happened in adolescence one of which is the phsicological and social changes and teenagers had a great curiosity about sexual matters. To fulfill their curiocity of those they seek an information from various sources including mass media and electronic media. The influence of mass media is often adopted by young people in their daily sexual interaction. The television programs most frequently watched by adolescence was Korean movies, that is one of threat here since 2012, and it also brings some change in teenage dating behavior that adopted from Korean movies ?âObjective: To get a description about the stage of teenage dating behavior who was adopted from Korea drama movie boys before flower in SMAN 2 KupangMethod : This research was a descriptive research with cross sectional design, Population of the research is all girl teenage in the second level in SMAN 2 Kupang. The sample of this research are 48 person and data collect by using questioner.Result : the stage of the highest teenage datingcompliance with Korean drama series BBF is the first date (63,7%) and the lowest compliance is at the stage of introductions 62%.Conclusion : Most of the dating behavior adopted by the Korean drama BBF is that equal to 63%.